2016
DOI: 10.1108/ijlm-04-2014-0063
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of logistics service quality in freight forwarding companies

Abstract: Purpose The purpose of this paper is to determine how customers from different market segments assess the quality of freight forwarding services, depending on the structure of services, as well as the mutual relation between the freight forwarder and the customers. Design/methodology/approach The research is based on the SERVQUAL model and surveys. The methodology for measuring the quality of logistics services in freight forwarding companies is developed. On the basis of the proposed methodology, the empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(59 citation statements)
references
References 80 publications
(103 reference statements)
3
52
0
4
Order By: Relevance
“…The SERVQUAL model and LSQ model are currently the two most researched ones [26]. Kilibarda et al develop a modified SERVQUAL model for measuring the LSQ in freight forwarding companies [27]. Gajewska and Grigoroudis apply the integrated SERVQUAL model and ordered weighted averaging technique to evaluate the performance of logistics services in the refrigerated transport industry (from the perspective of refrigerated transport companies) [28].…”
Section: Dimensions and Indices Of Evaluation Modelmentioning
confidence: 99%
“…The SERVQUAL model and LSQ model are currently the two most researched ones [26]. Kilibarda et al develop a modified SERVQUAL model for measuring the LSQ in freight forwarding companies [27]. Gajewska and Grigoroudis apply the integrated SERVQUAL model and ordered weighted averaging technique to evaluate the performance of logistics services in the refrigerated transport industry (from the perspective of refrigerated transport companies) [28].…”
Section: Dimensions and Indices Of Evaluation Modelmentioning
confidence: 99%
“…The authors proposed the more specific logistics management standards may be needed to improve the process. Kilibarda et al (2016) use SERVQUAL model to evaluate the logistics service quality of freight forwarder. Factor analysis and ANOVA are conducted to explore best service quality items.…”
Section: Methodsmentioning
confidence: 99%
“…Prentkovskis et al [26] proved the applicability of the SQ model in combination with a MCDM method using the example of a logistics service in an express post company. In their research applying SERVQUAL, Kilibarda et al [27] proved that the quality of logistics services was not at a satisfactory level in Serbia. Using SERVQUAL, Knop [28] showed that the quality of the service provided by transport and logistics operators in the pharmaceutical industry was such that the expectations regarding the quality of services provided by these operators were higher than the actual quality level obtained for all dimensions of the service quality being evaluated.…”
Section: Literature Reviewmentioning
confidence: 99%